Bataknese Women’s Language Attitude in Movie Lamaran : A Sociolingustics Study - Sekar Arum Garnasih; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study are to analyze The Use Of Bataknese women’s language attitudes occurs in the movie Lamaran and the type of meaning from the source taken from the official movie script. The method is used in this study is descriptive analysis method. By using Holmes (1992:317) says that some researchers report that women use fences up to three times more often than men, while others have no difference between the sexes, and from the sociolinguistic perspective, language attitude in multilingual society is an interesting phenomenon to study, Speaking activities will be more successful if they are supported by other factors that also determine, such as a good attitude and situation (Jabeen, 2011). The research reveals of two findings. The use woman’s language and language attitude. A diglossia consists of a high and low language. The high language is used for specific purposes such as business transactions, ceremonies, and religious rites. The low language is used for everyday conversation. Language attitudes are evaluative reactions to different language varieties. They reflect, at least in part, two sequential cognitive processes: social categorization and stereotyping. the results of the study reveal that the tradition and culture of the Batak is still strong. The culture of the Batak people still believes that the Marga is one that must be owned by the Batak people because it shows their descendants. Batak people always speak loudly because they have strong, wise and familial personalities.